BCR-ABL Mutations in Chronic Myeloid Leukemia Treated With Tyrosine Kinase Inhibitors and Impact on Survival. (21st October 2015) - Pagnano, Katia Borgia Barbosa; Bendit, Israel; Boquimpani, Carla; De Souza, Carmino Antonio; Miranda, Eliana C M; Zalcberg, Ilana; Larripa, Irene; Nardinelli, Luciana; Silveira, Rosana Antunes; Fogliatto, Laura; Spector, Nelson; Funke, Vaneuza; et al.
Abstract : This is the largest Latin American study of BCR-ABL mutations in chronic myeloid leukemia (CML) patients, resistant to imatinib (IM). In 195/467 (41%) patients, mutations were detected. The most frequent mutation was T315I ( n = 31, 16%). Progression-free (PFS) and overall survival (OS) at 5 years were lower in patients with BCR-ABL mutations (43% vs. 65%, p = 0.07 and 47% vs. 72%, p = 0.03, respectively) and in those with the T315I mutation ( p = 0.003 and p = 0.03). OS and PFS were superior in subgroup who switched to second generation inhibitors (SGIs) after IM failure (OS: 50% vs. 39% p = 0.01; PFS: 48% vs. 30% p = 0.02). BCR-ABL mutations conferred a significant poor prognosis in CML patients.